Multiply charged naphthalene and its C10H8 isomers: bonding, spectroscopy, and implications in AGN environments. Issue 4 (12th March 2022) - Santos, Julia C; Fantuzzi, Felipe; Quitián-Lara, Heidy M; Martins-Franco, Yanna; Menéndez-Delmestre, Karín; Boechat-Roberty, Heloisa M; Oliveira, Ricardo R
ABSTRACT: Naphthalene (C10 H8 ) is the simplest polycyclic aromatic hydrocarbon (PAH) and an important component in a series of astrochemical reactions involving hydrocarbons. Its molecular charge state affects the stability of its isomeric structures, which is specially relevant in ionized astrophysical environments. We thus perform an extensive computational search for low-energy molecular structures of neutral, singly, and multiply charged naphthalene and its isomers with charge states + q = 0–4 and investigate their geometric properties and bonding situations. We find that isomerization reactions should be frequent for higher charged states and that open chains dominate their low-energy structures. We compute both the scaled-harmonic and anharmonic infrared (IR) spectra of selected low-energy species and provide the calculated scaling factors for the naphthalene neutral, cation, and dication global minima. All simulated spectra reproduce satisfactorily the experimental data and, thus, are adequate for aiding observations. Moreover, the potential presence of these species in the emission spectra of the circumnuclear regions of active galactic nuclei (AGNs), with high energetic X-ray photon fluxes, is explored using the experimental value of the naphthalene photodissociation cross-section, σ ph − d, to determine its half-life, t 1/2, at a photon energy of 2.5 keV in a set of relevant sources. Finally, we show that the computed IR bands of the triply and quadruply charged species are able to reproduce some features of the selected AGN sources.